PENGARUH PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI (E-LEARNING) TERHADAP NILAI AKADEMIK MATA PELAJARAN FIKIH SISWA KELAS VII MTS AL IKHWANUL MUSLIMUN SECANGGANG - Habibah; Diani Syahfitri; Syahrul Affan (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
This shows a positive and significant relationship. The academic scores of students at MTs Ikhwanul Muslimin have an average result of 53.2, the median is 53.9, the mode is 53.1, the variance is 18.76 and the standard deviation is 4.33 which is acceptable with significant tolerance limits. This shows a positive and significant relationship. There is a positive and significant relationship between the variable utilization of E-Learning applications and students' academic grades at MTs Ikhwanul Muslimin Secanggang District with a regression line Y=21.84 +0.62 X. There is a significant correlation between the utilization of E-Learning applications and academic grades students in the fiqh subject at MTs Ikhwanul Muslimin Secanggang